Enhanced Anticancer Response of Curcumin- and Piperine-Loaded Lignin-g-p (NIPAM-co-DMAEMA) Gold Nanogels against U-251 MG Glioblastoma Multiforme - Bilal Javed (MDPI AG, 2021)
Glioblastoma multiforme (GBM) is the most aggressive and commonly diagnosed brain cancer and is highly resistant to routine chemotherapeutic drugs. The present study involves the synthesis of Lignin-g-p (NIPAM-co-DMAEMA) gold nanogel, loaded with curcumin and piperine, to treat GBM. The ongoing study has the application potential to (1) overcome the limitations of drugs biodistribution, (2) enhance the toxicity of anticancer drugs against GBM, and (3) identify the drugs uptake pathway. Atom transfer radical polymerization was used to synthesize the Lignin-g-PNIPAM network, crosslinked with the gold nanoparticles (GNPs) to self-assemble into nanogels. The size distribution and morphological analysis confirmed that the drug-loaded gold nanogels are spherical and exist in the size of 180 nm. The single and combinatorial toxicity effects of curcumin- and piperine-loaded Lignin-g-p (NIPAM-co-DMAEMA) gold nanogels were studied against U-251 MG GBM cells. A cytotoxicity analysis displayed anticancer properties. IC50 of curcumin- and piperine-loaded gold nanogels were recorded at 30 μM and 35 μM, respectively. Immunostaining and Western blot analysis confirmed the protein expression of caspase-3 and cleaved caspase-3 in cells treated with drug-loaded nanogels. Kinetic drug release revealed 86% release of hybrid curcumin–piperine from gold nanogel after 250 min at pH 4. Atomic absorption spectroscopic analysis confirmed that the drug-loaded nanogels have better internalization or association with the cancer cells than the GNPs or nano-gels alone. Morphological studies further confirmed that the curcumin and piperine nanogels penetrate the cells via endocytic pathways and induce caspase-3-related apoptosis. The experimental evidence shows the enhanced properties of combinatorial curcumin–piperine gold nanogels (IC50: 21 μM) to overcome the limitations of conventional chemotherapeutic treatments of glioma cells.